Activity of Birinapant, a SMAC Mimetic Compound, Alone or in Combination in NSCLCs With Different Mutations - Colombo, Marika; Marabese, Mirko; Vargiu, Giulia; Broggini, Massimo; Caiola, Elisa (Frontiers in Oncology, 2020)
Liver kinase B1 (LKB1/STK11) is the second tumor suppressor gene most frequently mutated in non-small-cell lung cancer (NSCLC) and its activity is impaired in about half KRAS-mutated NSCLCs. Nowadays, no effective therapies are available for patients having these mutations. To highlight new vulnerabilities of this subgroup of tumors exploitable to design specific therapies we screened an US FDA-approved drug library using an isogenic system of wild-type (WT) or deleted LKB1. Among eight hit compounds, Birinapant, an inhibitor of the Inhibitor of Apoptosis Proteins (IAPs), was the most active compound in LKB1-deleted clone only compared to its LKB1 WT counterpart. We validated the Birinapant cells response and its mechanism of action to be dependent on LKB1 deletion. Indeed, we demonstrated the ability of this compound to induce apoptosis, through activation of caspases in the LKB1-deleted clone only. Expanding our results, we found that the presence of KRAS mutations could mediate Birinapant resistance in a panel of NSCLC cell lines. The combination of Birinapant with Ralimetinib, inhibitor of p38α, restores the sensitivity of LKB1- and KRAS-mutated cell lines to the IAP inhibitor Birinapant. Our study shows how the use of Birinapant could be a viable therapeutic option for patients with LKB1-mutated NSCLCs. In addition, combination of Birinapant and a KRAS pathway inhibitor, as Ralimetinib, could be useful for patients with LKB1 and KRAS-mutated NSCLC.